Psychedelics and cognitive function: A systematic review (Research, Society and Development, 2023)
Introduction: With the progressive advancement of clinical and experimental trials aimed at investigating the pharmacotherapeutic potential of psychedelic substances, there is also the development of other conceptions of use, not only for the treatment of psychiatric disorders, but also for the improvement of emotional/cognitive functions. Objective: The present study is a systematic review of investigations aimed at evaluating the effects of psychedelics on cognitive functions in healthy volunteers. Methods: A search was performed in PubMed database, using the search terms “psychedelics and cognitive enhancement” and “psychedelics and cognitive performance”. Results and conclusions: Of the experimental studies analyzed, only forty-six (46) met the inclusion criteria. The results obtained showed that 3,4-methylenedioxy-methamphetamine (MDMA) was the most studied drug, with eighteen (18) articles. Fourteen (14) articles were published with psilocybin. Lysergic acid diethylamide (LSD) ranked third, with six (6) articles; other two (2) studies focused on investigating the beverage ayahuasca, and another (1) its psychoactive-containing molecule: dimethyltryptamine (DMT). Eight (8) studies investigated the effects of other psychedelic drugs, like S-ketamine, mescaline, 3,4-methylenedioxy-amphetamine (MDE), and ibogaine. Although there were no serious adverse effects resulting from the use of the investigated psychedelic drugs, rigorous assessment of the potential risks of long-term use and of the advantages of the continuous use of these drugs through neuropsychological assessments are still warranted.